2003
DOI: 10.1016/s0016-7061(03)00069-7
|View full text |Cite
|
Sign up to set email alerts
|

Lead(II) retention by Alfisol and clinoptilolite: cation balance and pH effect

Abstract: Lead (Pb 2 + ) sorption by Alfisol and zeolite was studied at pH 3, 4, and 5 to find the relationship between the amounts of Pb retained and ions displaced from the soil into the solution. In Alfisol Pb sorption was accompanied by the increase in contents of both Ca 2 + and H + constituting about 2/3 and 1/3 of the total amount of displaced cations, respectively. Increase in pH enhanced sorption of Pb. Hystersis of lead adsorption was observed in Alfisol. Clinoptilolite zeolite sorbed 20 -30 times more Pb than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 12 publications
4
23
0
Order By: Relevance
“…Ponizovsky and Tsadilas, 2003;Ouki and Kavannagh, 1997;Mondale et al, 1995). Higher selectivity was reported for Pb 2+ by clinoptilolite compared to Zn 2+ (Langella et al, 2000;Mondale et al, 1995), in line with our findings.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Ponizovsky and Tsadilas, 2003;Ouki and Kavannagh, 1997;Mondale et al, 1995). Higher selectivity was reported for Pb 2+ by clinoptilolite compared to Zn 2+ (Langella et al, 2000;Mondale et al, 1995), in line with our findings.…”
Section: Resultssupporting
confidence: 92%
“…So far, several studies were reported in literature regarding different aspects of the adsorption behavior of Zn 2+ and Pb 2+ by kaolinite and clinoptilolite (e.g. Mier et al, 2001;Mondale et al, 1995;Ouki and Kavannagh, 1997;Ponizovsky and Tsadilas, 2003;Coles and Yong, 2002;Langella et al, 2000;Ikhsan et al, 1999;Hooda and Alloway, 1998;Holm and Zhu, 1994). Our literature survey indicated a scarcity in the available data regarding the uptake of these ions by MgCO 3 (e.g.…”
Section: Introductionmentioning
confidence: 75%
“…These behaviors caused a decrease in the pH. Ponizovsky and Tsadilas [7] showed that ion exchange was the only possible mechanism for the lead retention on clinoptilolite rich natural zeolitic material in various pH values. Doula and Ioannou [8] investigated the effects of electrolyte anion on Cu adsorption-desorption by clinoptilolite rich natural zeolitic material.…”
Section: Introductionmentioning
confidence: 99%
“…According to the aims of the present work, the sorbent mass and solution volume were reasonably low as it is usual in analytical methodologies. On the other hand, pH of solution of 5 was selected, according to previous experiences (Ponizovskya and Tsadilas 2003). The mean sorption capacity (n = 3) and absolute standard deviation for treated and non-treated zeolites and for each concentration of lead in solution are represented in Fig.…”
Section: Resultsmentioning
confidence: 99%